Write a Scientific Paper (WASP): Miscellaneous practical and material aspects – part 2. (February 2019) - Grech, Victor
Abstract: This WASP (Write a Scientific Paper) Best Practice Guidelines (BPG) will wrap up all of the aspects pertaining to qualitative analyses as well as some more theoretical aspects of paper writing. These include types of studies and their importance in the hierarchy of evidence base as practiced in medicine. In addition, two papers review very practical aspects of paper writing including which journals to target (and why), and realistic methods for dealing with editors. Another paper also deals with fraud and hoax in science. Since the next BPG collection pertaining to WASP will deal with qualitative methods of analysis, by way of introduction to different ways of doing things, this collection will also review the practical differences between writing and presentation in the humanities and in the sciences. A paper will also very briefly review interdisciplinarity, including the depiction of interdisciplinarians as envisaged in future, in the (albeit speculative) science fiction genre. A final paper will demonstrate several precepts that have been highlighted over these BPGs, utilising as a practical example, a novel study that uses past requirements in order to estimate anticipated trends in cardiology service requirements at Mater Dei Hospital, Malta.